What Are the Consent Requirements for AI Healthcare Applications? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2019)
The integration of Artificial Intelligence (AI) into healthcare is revolutionizing diagnostics, treatment, and patient management, but it also brings to the ...
Keywords: Healthcare Data Privacy and Security; Consent; Requirements; Healthcare; Artificial Intelligence; Digital Health; Diagnostics